Ovarian nutritional resources during the reproductive cycle of the hematophagous Dipetalogaster maxima (Hemiptera: Reduviidae): focus on lipid metabolism - Leyria, Jimena (2014)
In this study, we have analyzed the changes of the ovarian nutritional resources in Dipetalogaster maxima at representative days of the reproductive cycle: previtellogenesis, vitellogenesis, as well as fasting-induced early and late atresia. As expected, the amounts of ovarian lipids, proteins, and glycogen increased significantly from previtellogenesis to vitellogenesis and then, diminished during atresia. However, lipids and protein stores found at the atretic stages were higher in comparison to those registered at previtellogenesis. Specific lipid staining of ovarian tissue sections evidenced remarkable changes in the shape, size, and distribution of lipid droplets throughout the reproductive cycle. The role of lipophorin (Lp) as a yolk protein precursor was analyzed by co-injecting Lp-OG (where OG is Oregon Green) and Lp-DiI (where DiI is 1,10-dioctadecyl-3,3,30,30-tetramethylindocarbocyanine) to follow the entire particle, demonstrating that both probes colocalized mainly in the yolk bodies of vitellogenic oocytes. Immunofluorescence assays also showed that Lp was associated to yolk bodies, supporting its endocytic pathway during vitellogenesis. The involvement of Lp in lipid delivery to oocytes was investigated in vivo by co-injecting fluorescent probes to follow the fate of the entire particle (Lp-DiI) and its lipid cargo (Lp-Bodipy-FA). Lp-DiI was readily incorporated by vitellogenic oocytes and no lipoprotein uptake was observed in terminal follicles of ovaries at atretic stages. Bodipy-FA was promptly transferred to vitellogenic oocytes and, to a much lesser extent, to previtellogenic follicles and to oocytes of ovarian tissue at atretic stages. Colocalization of Lp-DiI and Lp-Bodipy-FA inside yolk bodies indicated the relevance of Lp in the buildup of lipid and protein oocyte stores during vitellogenesis.